Efficacy of Two Different Views of Video Demonstration in Teaching Access Cavity Preparation to Third Year Dental Students - Dabbour, Hazem; Liew, Amy Kia Cheen; Soo, Eason; Abdullah, Dalia (Iranian Endodontic Journal, 2018)
Introduction: Demonstration of the access cavity preparation procedures to dental students is challenging due to the limited operating field and the detailed nature of the procedures. The aim of this study was to develop and evaluate two different views in video demonstrations used to teach access cavity preparation. Methods and Materials: Two videos of access cavity preparation were filmed, one showing the occlusal view (OV) and one showing the sectional view (SV). Third-year dental students (n=57) who consented to participate in the study were divided into two groups to watch one of the videos. The perception and performance of both groups were compared using the Mann-Whitney U test and Fisher’s exact test. Results: At baseline, group OV (n=29) and group SV (n=28) were not significantly different in terms of operative scores (P=0.330). After watching the videos, the basic understanding of the theories was similar in both groups. However, the SV group responded more positively towards the helpfulness of the video in visualizing the inner anatomy of the tooth and in implementing the procedures (P<0.05). The SV group also completed the exercise within a shorter time (P<0.001). Nevertheless, the quality of the prepared access cavities was not significantly different between groups. Conclusion: Within the limitations of this study, the additional step in sectioning a tooth before demonstration of access cavity preparation seems well worth the effort, offering the novice students advantages in visualizing certain anatomical landmarks and implementing access cavity preparation procedure within a shorter timeframe. Nevertheless, it did not improve the final quality of the preparations. Keywords: Access Cavity; Dental Education; Endodontics; Root Canal Therapy; Video Demonstration